Mazak Laser, the Story so Far: Interview on the company's laser development with Gaetano Lo Guzzo, Director Mazak Laser Europe. Issue 2 (12th April 2017) - Unknown
Abstract: The last three years have seen significant change in Mazak's laser business across Europe, not least the decision to combine the division with machine tools. We meet Gaetano Lo Guzzo, Director Mazak Laser Europe, to find out more.